Efektivitas Layanan Bimbingan Kelompok dengan Modeling dalam Meningkatkan Efikasi Diri Siswa dalam Menghadapi Ujian - Anggara, Fery; Yusuf, A. Muri; Marjohan, Marjohan (Konselor, 2016)
Self-Efficacyis the most important factorforstudents’successto face examination,becauseself-efficacy beliefs made a powerful and independent contribution to the prediction of their academic performance.Modeling is one of technique usedto increase itandGroup guidancewas helpful in increasing students’ self-efficacy. This research sought to see the effectiveness of group guidance to increase the students’ self-efficacy through modeling to face examination. The subject of the research was 9 students in class XII of Pesantren Modern Diniyyah Pasia Assumed to have low self-efficacy.This research was classified into pre-experimental research which applied The One Group Pretest-Postest design. The treatment was given throuh modeling in eight meetings. The data were gathered by using self-efficacy scale which had been validated previously. The result of the research revealed that the application of group guidance service through modeling was effective to increase the students’ self-efficacy into better category. The students were confident about their ability to face examination, they were sure that they could maintain themselves, and they had confident to organize their ability to face other situation or condition.